The effect of hemodialysis on echocardiographic parameters and on supraventricular cardiac arrhythmias - Oleg V. Likhachev-Mishchenko (Concilium Medicum, 2020)
Relevance. Supraventricular arrhythmias are frequent comorbid conditions in patients with end-stage renal failure undergoing dialysis. The prevalence of atrial fibrillation (AF) in this group of patients is higher than in the general population and is associated with increased mortality.